The History of Success of Central Asian Company in Automobile Industry - Zhumanov, Kanat; Zhumanova, Anel; Yin-Fah, Benjamin Chan (Asian Business Review, 2018)
The paper analyzes the key success factors of automobile industry in Central Asia, Kazakhstan. In particularly, strategies used, experienced challenges faced by “Bipek Auto – Asia Auto” will be presented in this paper.
Keywords: Success factors; Kazakhstan; Auto Company